University of Évora in QA@CLEF-2004. - Quaresma, Paulo (2012)
The approach followed by the University of E ́vora team in order to build a system able to participate in the QA-CLEF task is described. The system is based in two steps: for each question, a first information retrieval task selects a set of potentially relevant documents; then, each of these documents is analysed trying to obtain their semantic represen- tation and the answer to the initial query. The proposed approach was applied to the test set of the QA-CLEF for the Portuguese language and the obtained results were quite interest- ing and motivating and allowed the identification of strong and weak characteristics of the system.